Pengaruh terapi aktivitas kelompok stimulasi persepsi terhadap kemampuan pasien mengontrol halusinasi di rumah sakit jiwa tampan Provinsi riau - Tiomarlina - Purba; Fathra Annis Nauli; Sri - Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this study is to determine the effect of stimulation of activity therapy perceptions of the patient's ability to control hallucinations . The research method is pre- experimental with one group pre - test and post - test design. The research is conducted at the Tampan Mental Hospital Riau Province on 26 respondents. The sampling method is cluster sampling technique. Measuring instruments is interview guides and observation sheets. The analysis is univariate and bivariate with dependent t test . The results showed the influence of group activity therapy stimulation perception of the patient's ability to control hallucinations ( p value = 0.000 ). Based on the result of this study, it is suggested to Tampan Mental Hospital Riau Province. Especially for nursing profession to apply group activity therapy mental disorders, especially in patients with hallucination problems. Keywords: Therapeutic activity stimulation group perception, hallucinations